The importance of fire refugia in the recolonization of a fire-sensitive conifer in northern Patagonia - Landesmann, Jennifer Brenda (2018)
Seed dispersal and seedling establishment are essential for plant recolonization after disturbances, especially for plants that rely exclusively on sexual reproduction such as post-fire colonizer trees. Fire refugia may play a key role not only allowing trees to survive fire, but also functioning as seed sources after it. The estimation of seed dispersal and seedling establishment are essential for assessing plant recolonization ability, understanding landscape dynamics and determining which areas may not be able to recover due to lack of seed arrival. Here we study the post-fire recolonization ability of Austrocedrus chilensis (Cordilleran Cypress) from fire refugia in burned areas of northwest Patagonia, Argentina. We mapped all female trees, saplings and seedlings within and around fire refugia, recorded the reproductive capacity of female trees and characterized the microsite conditions for establishment. We used an inverse modelling approach and Approximate Bayesian Computation to estimate the seed dispersal kernel and the probability of seedling establishment. We found that the average dispersal distance of an A. chilensis seed was 88.52 m. The dispersal kernel was fat-tailed, meaning that A. chilensis has the capacity of producing accelerating expansions. Large woody debris, litter, and the protection of shrubs were the most important factors associated with the presence of recruits. We highlight the importance of fire refugia as seed sources for the recolonization of burned areas and thus the relevance of protecting these places to allow the persistence of fire-sensitive species.